The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jvh.13405
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes and costs of a simplified antiviral treatment strategy for hepatitis C among monoinfected and HIV and/or hepatitis B virus‐co‐infected patients in Myanmar

Abstract: Access to hepatitis C virus (HCV) testing and treatment is limited in Myanmar. We assessed an integrated HIV and viral hepatitis testing and HCV treatment strategy. Sofosbuvir/velpatasvir (SOF/VEL) ± weight‐based ribavirin for 12 weeks was provided at three treatment sites in Myanmar and sustained virologic response (SVR) assessed at 12 weeks after treatment. Participants co‐infected with HBV were treated concurrently with tenofovir. Cost estimates in 2018 USD were made at Yangon and Mandalay using standard mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Low proportions of LTFUs were also reported by workers in other countries [44,45]. At present, we have to concede that the observed results were largely unexpected because treatment in these facilities is offered for free.…”
Section: Discussionmentioning
confidence: 58%
“…Low proportions of LTFUs were also reported by workers in other countries [44,45]. At present, we have to concede that the observed results were largely unexpected because treatment in these facilities is offered for free.…”
Section: Discussionmentioning
confidence: 58%
“…While lower than other cohorts in SSA, the rate of SVR among our participants is comparable to cohorts of PWID in other LMICs. PWID in an HCV treatment cohort in Myanmar achieved an overall SVR rate of 80% 7 . Similarly, 87% of a Bangladeshi HCV treatment cohort of PWID accessing harm services achieved SVR 8 .…”
Section: Discussionmentioning
confidence: 96%
“…PWID in an HCV treatment cohort in Myanmar achieved an overall SVR rate of 80%. 7 Similarly, 87% of a Bangladeshi HCV treatment cohort of PWID accessing harm services achieved SVR. 8 Furthermore, in an intent-to-treat analysis of HCV treatment services for high-risk groups in Ukraine, 78% of currently injecting PWIDs achieved SVR.…”
Section: Discussionmentioning
confidence: 99%
“…While adherence to HCV treatment was not measured, there was minimal loss to follow up; this may have been because of the Community Based Treatment model of care that incorporates a social worker into the clinical management team 18,19 and also provides harm reduction services at a community level. Even among PWID, who typically have high rate of loss to follow up 20 , there were few losses, due perhaps to the Community Based Treatment harm reduction program in Ukraine 19 . Other studies have demonstrated high rates of success with HCV treatment co-located with substance use treatment services and amongst PWID receiving OST 21,22 .…”
Section: Discussionmentioning
confidence: 99%